Spirulina Based Iron Oxide Nanoparticles for Adsorptive Removal of Crystal Violet Dye - Bhukal, Santosh; Sharma, Anuj; Rishi; Divya; Kumar, Sumit; Deepak, Bansal; Pal, Kaushik; Mona, Sharma (Topics in catalysis, 2022)
In comparison to algal biomass, algae-based nanoparticle (green synthesis) not only aids in the removal of toxins from wastewater, but it is also an ecologically benign strategy with enhanced efficacy. In the present study, Spirulina is being utilised to make green iron oxide nanoparticles (S-IONPs), which further used to make an effective adsorbent for the removal of cationic crystal violet (CV) dye using ultra-sonic waves. The created nano-adsorbent was thoroughly investigated using a variety of characterisation techniques, including FT-IR, XRD, FE-SEM, and UV–VIS spectroscopy. Moreover, the S-IONPs adsorbent performed remarkably well in removing key chemicals from synthetic solutions, such as dyes. The pseudo-second order model was used to describe the kinetic profile, while the linearized Langmuir theory with r 2 of 0.96413 and q max of 55.62 mg/g was used to show the adsorption isotherm. Sequestration of the CV dye from aqueous solution using S-IONPs was carried out efficiently. The potential of S-IONPs for decolorization of crystal violet dye solution was also confirmed through various analytical techniques. Graphical Abstract Preparation of Spirulina based iron oxide nanoparticles for sequestration of Crystal Violet dye from aqueous solution